PATIENT HEALTH AND MEDICAL PRACTITIONER PRESCRIBED DRUG PROVIDING - Jitendra, Ladi; Baskar, Radhika (International Journal of Psychosocial Rehabilitation, 2020)
Current advances in biomedical engineering and the science and technology of materials have brought about the creation of novel bioactive materials by which the doctor himself can follow the proper guidance. When managing various rates of medications for different people that shape nervous disorders or strokes that cause people worried to die. In order to create drug handling's restriction actions, we handle a biomedical sensor that can be vividly controlled by individuals. This research focuses on examining patient safety in remote areas, and we can also serve pharmacy-only medication prescribed by the pharmacy.